2017
DOI: 10.1053/j.semnuclmed.2017.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Metabolism In Vivo Using Endogenous 11 C Metabolic Tracers

Abstract: Cancer and other diseases are increasingly understood in terms of their metabolic disturbances. This thinking has revolutionized the field of ex vivo metabolomics and motivated new approaches to detect metabolites in living systems including proton magnetic resonance spectroscopy (1H-MRS), hyperpolarized 13C MRS, and positron emission tomography (PET). For PET, imaging abnormal metabolism in vivo is hardly new. Positron-labeled small-molecule metabolites have been used for decades in humans, including 18F-FDG,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…Methionine is a sulfur-containing amino acid that can be rapidly synthesized without complicated purification steps . Numerous synthetic pathways can be used based on the alkylation of the corresponding sulfide anion of l -homocysteine with either [ 11 C]­CH 3 I (Figure ) or [ 11 C]­CH 3 OTf . Moreover, l -[ methyl - 11 C]­methionine can be efficiently produced by 11 C-methylation of l -cysteine thiolactone hydrochloride or l -homocysteine in solution using the “bubbling” method, on a solid-phase extraction cartridge or by using the captive solvent method (“in the loop”) with or without semipreparative HPLC purification.…”
Section: Amino Acidsmentioning
confidence: 99%
“…Methionine is a sulfur-containing amino acid that can be rapidly synthesized without complicated purification steps . Numerous synthetic pathways can be used based on the alkylation of the corresponding sulfide anion of l -homocysteine with either [ 11 C]­CH 3 I (Figure ) or [ 11 C]­CH 3 OTf . Moreover, l -[ methyl - 11 C]­methionine can be efficiently produced by 11 C-methylation of l -cysteine thiolactone hydrochloride or l -homocysteine in solution using the “bubbling” method, on a solid-phase extraction cartridge or by using the captive solvent method (“in the loop”) with or without semipreparative HPLC purification.…”
Section: Amino Acidsmentioning
confidence: 99%
“…For 11 C metabolites, structures can be generated that are chemically identical to those of their parent molecules. 27 This strategy is also a key feature of the most commonly used PET radiotracer, [ 18 F]FDG, which is a substrate for both glucose transporters (GLUTs) and hexokinase. Many radionuclides have been used to image infection, including 11 C (PET, t 1/2 = 20 min), 68 Ga (PET, t 1/2 = 68 min), 18 F (PET, t 1/2 = 110 min), 99m Tc (SPECT, t 1/2 = 6 h), 64 Cu (PET, t 1/2 = 13 h), 111 In (SPECT, t 1/2 = 67 h), 201 Tl (t 1/2 = 73 h), 67 Ga (SPECT, t 1/2 = 78 h), With respect to the bacterial cell wall, several recent studies have demonstrated the synergy of optical and nuclear imaging.…”
Section: Fluorescence: the Origin Of Nuclearmentioning
confidence: 99%
“…This is particularly true for 11 C and 18 F radionuclei for which substitution likely induces fewer perturbations of biologic behavior. For 11 C metabolites, structures can be generated that are chemically identical to those of their parent molecules . This strategy is also a key feature of the most commonly used PET radiotracer, [ 18 F]­FDG, which is a substrate for both glucose transporters (GLUTs) and hexokinase.…”
Section: Fluorescence: the Origin Of Nuclear Imaging Toolsmentioning
confidence: 99%
“…Because carbon is a component of biomolecules, labeling with the positron-emitting radioisotope carbon-11 ( 11 C) seems to be very attractive. Many attempts have been made to label glucose with radioisotope 11 C [60, 61]. [2- 11 C]-2-Deoxyglucose was developed as the 11 C counterpart of 18 F-FDG [62].…”
Section: Preclinical Development Of Glucose-based Radiopharmaceutimentioning
confidence: 99%